Improving marketability and quality of Sulemu soy milk: A community engagement approach to product diversification - Rahayu, Triastuti; Nurcahyanto, Guntur; Aryani, Ima; Suryani, Titik; Tyastuti, Erma Musbita; Sari, Siti Kartika; Maimun, Muhammad Halim; Ripdianti, Arum Dyah; Hardianto, Alden Ganendra Madhava Priya (Community Empowerment, 2025)
Original "SuleMu" soy milk currently has limited shelf life without refrigeration. Therefore, it is crucial to assist partners in enhancing product competitiveness and diversification. The primary objectives of this community engagement activity were to improve SuleMu's marketability through the addition of new flavors and the provision of nutritional value analysis, as well as to enhance product quality by developing derivative products such as soyghurt and frozen yogurt. The activity stages included: (1) mentoring for the diversification of SuleMu derivative products, (2) nutritional value analysis of derivative products, (3) designing product labels compliant with standards, and (4) conducting a market survey on consumer preferences for SuleMu derivative products. Results indicate that SuleMu is now available in new flavors: melon, chocolate, and strawberry. The nutritional content per 100 grams is 3.4–3.5 grams of soluble protein, 3.3–3.7 grams of fat, 5–5.7 grams of reducing sugars, 2.6–3.6 grams of crude fiber, and approximately 39–40 mg of calcium. SuleMu production increased from 5 kg of soybeans to 6 kg per day. Furthermore, consumers showed high interest in the "Soyoghurt" frozen yogurt derivative product, with 42.4% being very interested and positive evaluations regarding taste (36.1%) and affordable price (29.2%). Overall, this community engagement activity successfully increased SuleMu's production by 17%, and soyghurt demonstrates significant potential for development as a highly competitive new innovation.